Upaya Membangun Brand Awereness Dalam Rangka Mempengaruhi Keputusan Pembelian Konsumen Pada UMKM Penjaringansari - Daniel Putra Prastyawan; Yuniardi Rusdianto (Yayasan Daarul Huda Kruengmane, 2023)
In the current era of tight business market competition, which is very free and varied, it requires business actors to be more creative and compete in selling and marketing their business products. Business actors must create selected strategies that are considered the most effective and efficient in order to maintain the products offered for sustainable use by consumers. Therefore, it is considered important to have product branding carried out by business actors in order to build Brand awareness that will be owned by every consumer. Brand awareness is also the ability of a prospective buyer to recognize and remember that a brand is part of a particular product. This article aims to present information on how to build brand awareness to influence consumer purchasing decisions in Penjaringansari MSMEs.